ANALISIS KEBUTUHAN AIR BERSIH – STUDI KASUS PERENCANAAN JARINGAN PIPA DITRIBUSI DI DESA PENGALIHAN KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR DENGAN APLIKASI EPANET 2.0 - Suryadi , M. Gasali M (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2019)
Clean water is an important part of human life, so the availability of clean water is very influential for human life. The effect of the availability of clean water is not only on household needs, but also on the social, economic, and public facilities sectors, along with increasing population growth. Transfer Village is a village located in Keritang District with a village area of ​​77.15 Km2, with a population in 2015 of 7,146 people. With the increasing number of population each year getting higher, the need for clean water also increases. Pipeline design using the EPANET 2.0 application is expected to be able to answer the need for minung water in the study area. From the results of the study it was found that the discharge of clean water projection results in 2025 with 100% service level and 90 liters / person / day needs, average needs in the amount of 13.02 liters / second, the maximum daily requirement is 14.97 liters / second and the peak hour requirement is 21.48 liters / second